Exploring lake ecological water levels via the Lake Ecological Comprehensive Evaluation Index (LECEI) approach in conjunction with terrestrial and aquatic environments - Weifeng Yue; Changming Cao; Qingqing Fang; Guoqiang Wang; Ziyi Zan; Kun Wang; Tingxi Liu (Ecological Indicators)
Determining ecological water levels crucially lies in elucidating the relationship between water levels and ecological environmental quality, which are essential for the sustainable development of lake ecosystems. However, the response of lake environmental quality to water level fluctuations remains incompletely understood. This study employed forward and inverse modelling of remote sensing data at large spatiotemporal scales to propose a novel comprehensive evaluation framework, the Lake Ecological Comprehensive Evaluation Index (LECEI), which characterises lake environmental quality by integrating the terrestrial (lakeshore zones that are assessed using the remote sensing ecological index, RSEI) and aquatic (water bodies that are assessed using lake water quality indicators, LWQIs) indicators. The upper limit, lower limit, and optimal ecological water levels were subsequently quantitatively determined on the basis of the nonlinear relationship between the water level and the LECEI. This study revealed correlation coefficients between the LECEI and water levels ranging from 0.77 to 0.79 for Wuliangsuhai Lake from 1990 to 2017. Additionally, the upper and lower ecological water levels were determined to be 1018.77 m and 1019.23 m, respectively, by an analysis of the probability density distribution of the LECEI in conjunction with its nonlinear relationship with the water level. Furthermore, this study examined the relationship between the LECEI and water level elevation and identified 1019.13 m as the optimal ecological water level for maintaining lake environmental quality, indicating an inflection point from a slow to a significant increase in the LECEI. By employing this novel comprehensive evaluation framework, this study successfully determined the ecological water levels of the lake, thereby supporting the maintenance of health and sustainable development of lake ecosystems.